PERILAKU PENOREHAN RANGGAH PADA TUMBUHAN OLEH RUSA BAWEAN (Axis kuhlii) - Gono Semiadi; Kustoto; I Ketut Sutama; Burhanudin Masyud (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 1997)
The behavior of antler rubbing in the Cervidae family during the period of hard antlers is related to the territorial marking and reproductive activity. Bawean deer (Axis kuhlii) is one of the rarest animals in Indonesia and endemic to Bawean Island. The knowledge of their biology in the natural habitat is scarce. The objective of this study is to understand on their behavior, particularly the stags during their hard antlers period by observing their rubbing activities on the plantations in their natural habitat. Data collections were conducted in four sites, from June 1996 to October 1996, through monthly visit. Transects with the length of 900 to 2000 m and width of 100 m were established. Observation took place every 100 m along the transect in both sides on the area of 25m2.. the name of local plants which were rub was noted, the length and width of the rubbing marks on the plants and the diameter of the plant were measured. The result showed there were 22 species (in which 7 were unidentified) of plants being rub by the deer. The highest intensity is on Macu (15%) followed by Ngos-ngosan and Sentol (11% each). Number of death plants due to rubbing activity was very low (<1%). Mean of the plants diameter being rub was 19.1 mm, with the length and total area being rub were 19.1 mm and 6521 mm2, respectively. From this study it can be concluded that stags rub the plants during their hard antlers period on the bushy type category. The rutting season for Bawean stags in their habitat was estimated between May to November.